Analysis of Moral Crisis in Elementary School in the Millennial Era - Fajar Budiyono; Syaiful Bahri; Sama' Sama' (Universitas Muhammadiyah Enrekang, 2022)
The moral crisis is the fading of attitudes, character and behavior that are sustainable with the goodness of each individual. The moral crisis that occurred among elementary school students, for example, was the loss of the culture of saying the words